Exploring Creating Shared Value in Corporate Social Responsibility Initiatives: A Case Study of PT Nusa Halmahera Minerals - Ruliyanto Syahrain; Muhammad Hasnin; Faradisa Bachmid (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to look at the governance of the implementation of the Community Development and Empowerment Program from the point of view of Creating Shared Value. This qualitative research involves PT Nusa Halmahera Mineral and the community around the mine. Data collection techniques, namely observation, interviews, and document review. The results showed that PT NHM's Community Empowerment Program had 8 programs, and only 5 were realized. After being analyzed, PT NHM's Community Development and Empowerment Program (PPM) has carried out the practice of Creating Shared Value in three stages: redefining products and markets, redefining productivity in the value chain and developing local clusters. These programs have positively impacted the lives of the people in the 5 districts surrounding the mine.